Development of a Web-Based Application for Identifying Sport Talent in Children Aged 11-15 Years - Septian Dwi Yusdiantara; Tommy Soenyoto (Journal of Physical Education and Sports, 2026)
The identification of athletic talent at the school level in Indonesia still relies heavily on the subjective observations of physical education teachers and coaches, with limited use of data analysis technology. This situation has the potential to lead to inaccuracies in talent guidance and inefficient coaching decisions. This study aims to develop and evaluate the feasibility and effectiveness of the SIBAKAT ID web-based application as a tool for identifying athletic talent in children aged 11–15 years through the processing of biomotor and anthropometric data using the Sport Search method. This study uses a Research and Development approach that includes needs analysis, system design, expert validation, small-scale trials, and large-scale trials. The research subjects involved physical education teachers, coaches, and sports academics. The data were analyzed using quantitative and qualitative descriptive techniques. The results showed that the SIBAKAT ID application had a very high level of feasibility in terms of material suitability and media quality based on the results of expert validation and user trials. Effectiveness tests show that the application is capable of systematically processing test data, displaying talent potential rankings, and providing efficient sports branch recommendations. It can be concluded that the SIBAKAT ID application is feasible and effective for use as a data-based decision-making support tool in the process.